Development of a capillary electrophoresis method for the separation of flavonolignans in silymarin complex - Riasová, Petra; Jenčo, Jaroslav; Moreno-González, David; Vander Heyden, Yvan; Mangelings, Debby; Polášek, Miroslav; Jáč, Pavel (Electrophoresis, 2022)
CE method for the baseline separation of structurally similar flavonolignans silybin A, silybin B, isosilybin A, isosilybin B, silychristin, silydianin, and their precursor taxifolin in silymarin complex has been developed and validated. The optimized background electrolyte was 100 mmol/L boric acid (pH 9.0) containing 5 mmol/L heptakis(2,3,6-tri-O-methyl)-β-CD and 10% (v/v) of methanol. The separation was carried out in an 80.5/72 cm (50 μm id) fused silica capillary at +25 kV with UV detection at 200 nm. Genistein (10 μg/mL) was used as internal standard. The resolution between the diastereomers of silybin and isosilybin was 1.73 and 2.59, respectively. The method was validated for each analyte in a concentration range of 2.5-50 μg/mL. The calibration curves were rectilinear with correlation coefficients ≥0.9972. The method was applied to determine flavonolignans in two dietary supplements containing Silybum marianum extract. The accuracy was evaluated by comparing the results of the CE analyses of the dietary supplements with those of the reference United States Pharmacopeial HPLC method. The unpaired t-test did not show a statistically significant difference between the results of both the proposed CE and the reference method (p > 0.05, n = 3).
Keywords: CE; ostropestřec mariánský; Silybum marianum; vysokoúčinná kapalinová chromatografie; Silymarin; Heptakis(2,3, 6-tri-O-methyl)-β-CD; Antioxidants; Chromatography, High Pressure Liquid; Flavonolignans; Electrophoresis, Capillary; Dietary supplements; silymarin; antioxidancia; elektroforéza kapilární